Engineered Bacteria-Based Living Materials for Biotherapeutic Applications - Omer, Rabia; Mohsin, Muhammad Zubair; Mohsin, Ali; Mushtaq, Bilal Sajid; Huang, Xumeng; Guo, Meijin; Zhuang, Yingping; Huang, Jiaofang (Frontiers in Bioengineering and Biotechnology, 2022)
Future advances in therapeutics demand the development of dynamic and intelligent living materials. The past static monofunctional materials shall be unable to meet the requirements of future medical development. Also, the demand for precision medicine has increased with the progressively developing human society. Therefore, engineered living materials (ELMs) are vitally important for biotherapeutic applications. These ELMs can be cells, microbes, biofilms, and spores, representing a new platform for treating intractable diseases. Synthetic biology plays a crucial role in the engineering of these living entities. Hence, in this review, the role of synthetic biology in designing and creating genetically engineered novel living material, particularly bacteria, has been briefly summarized for diagnostic and targeted delivery. The main focus is to provide knowledge about the recent advances in engineered bacterial-based therapies, especially in the treatment of cancer, inflammatory bowel diseases, and infection. Microorganisms, particularly probiotics, have been engineered for synthetic living therapies. Furthermore, these programmable bacteria are designed to sense input signals and respond to disease-changing environments with multipronged therapeutic outputs. These ELMs will open a new path for the synthesis of regenerative medicines as they release therapeutics that provide in situ drug delivery with lower systemic effects. In last, the challenges being faced in this field and the future directions requiring breakthroughs have been discussed. Conclusively, the intent is to present the recent advances in research and biomedical applications of engineered bacteria-based therapies during the last five years, as a novel treatment for uncontrollable diseases.